19. Innovative property for innovative land policy and urban design - Davy, Ben (AESOP, 2023)
Ben Davy is a former Chair of Land Policy, Land Management, and Municipal Geoinformation at the School of Spatial Planning at TU Dortmund University. He is a Visiting Professor of Law at the University of Johannesburg. Ben was President of the Association of European Schools of Planning (AESOP) (2018—2020) and of the International Academic Association on Planning, Law, and Property Rights (PLPR). His current research concerns land use ethics and South African land reforms. The event begins with a welcome speech by Prof. Christa Reicher and a short speech by Prof. Maria Håkansson, the AESOP‘s Vice President and Associate Professor in Urban and Regional Studies at KTH Royal Institute of Technology. WATCH THE FULL LECTURE AT THE VIMEO VIDEO LINK BELOW